INFORMATION SYSTEM DESIGN BASED WEB SERVICE DELIVERY IN RUSH COURIER SURABAYA - Fuad, Muhammad; sukmaaji, anjik; rahmawati, endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Service Delivery is one kind utilizing the service of a company in terms of delivery goods, which process comprises the transaction receipt of goods, packing of goods and delivery process. Which in process there are problems, such as delivery and transaction search process goods by the customer. Sometimes the customers want to know the process or position of the goods delivered. Based on the problems, then built a information system of services delivery using website. Soon, this application expected to help the user process, includes transaction process delivery services.